Enhancement of pinning and the peak effect in Y1–Fe Ba2Cu3O high-temperature superconductors - Pigalskiy, K.S.; Vishnev, A.A.; Efimov, N.N.; Shabatin, A.V.; Trakhtenberg, L.I. (Current applied physics, 2022)
Complex structural and magnetic studies of polycrystalline samples of the Y1-xFexBa2Cu3Oy high-Tc superconductor (x = 0, 0.02, 0.05) have been carried out in order to determine the effect of weak doping with a magnetic 3d ion on structural changes and the critical current density Jc. An increase in the Fe content results in a significant change in Jc and its field dependence. The dependences Jc(H) become nonmonotonic and demonstrate a pronounced peak (peak effect); as a result, the Jc increases strongly in wide temperature and magnetic field regions. The analysis of the field dependences of the pinning force reveals a scaling behavior. The parameters of the scaling function correspond to the point magnetic defects under strong effects of a thermally activated flux flow. Thus, the weak Fe doping (several molar percent) is a promising way to significant improvement of transport properties of high-Tc superconducting materials based on 123-type compounds. KCI Citation Count: 0